Herpetofauna of the Campus of the Universidade Federal do Espírito Santo, urban areas of Vitória, Brazil - Ferreira, Rodrigo Barbosa; Mendes, Sérgio Lucena (SITIENTIBUS série Ciências Biológicas, 2010)
The current study evaluates the composition of anuran and reptile assemblages in the central campus of the Federal University of Espírito Santo, municipality of Vitória. Field work was conducted monthly from January to December, 2005. Records were made by observation, vocalizations recording, and pitfall traps. Twelve anurans and eight reptiles were recorded: five lizards, two snakes, and one freshwater turtle. The herpetofauna was poorly diverse and consisted of generalist species, possibly due to the great influence of tides in several ponds. In addition, the history of anthropic occupation in the studied area altered or eliminated habitats to specialist species.